Analysis of The Influence of The Value of Non-Cash Payment Transactions on The Amount of Money Supply in Indonesia - Thoyyibah, Mazraaten; Wasiaturrahma (Journal of Developing Economies, 2024)
This literature explains the influence of credit card, debit card, and e-money transaction values on Indonesia’s M1 and M2 money supplies. Time series data from January 2010 to August 2023 are used taken from the official websites of Bank Indonesia and the Central Statistics Agency . The Vector Error Correction Model (VECM) is the analysis method employed. According to the study’s findings, the M1 and M2 money supply is significantly impacted by the value of debit card transactions in both the short and long term. While it has a large short-term impact on M1 and M2, the credit card transaction value variable has a negligible long-term impact on M2. In addition, the value of e-money transactions demonstrates that they have a large impact on M1 both in the short and long terms. On the other hand, it has a significant impact on M2 in the short term but not on M2 in the long run.